Optimalisasi Penerimaan Pajak BPHTB di Kabupaten Sikka: Analisis Implementasi dan Tantangan - Angela S. B. Mbiri; Imanuel Welem; Paulus Juru (sekolah Tinggi Ilmu Ekonomi Dharmaputra Semarang, 2025)
Bea Perolehan Hk Atas Tanah dan Bangunan (BPHTB) is one of the main sources of Regional Original Income (PAD) which is managed by the Sikka Regency Regional Revenue Agency (Bapenda). This research aims to analyze the optimization of BPHTB acceptance. The research method used is a qualitative approach with data collection techniques through interviews, observation and documentation studies. The research results show that the optimization efforts carried out, such as collaboration with notaries/PPATs, the use of technology through the